Progress in sustainable energy technologies: generating renewable energy - Midilli, Adnan; Kucuk, Haydar; Dincer, Ibrahim (Springer International Publishing, 2014)
This multi-disciplinary volume presents information on the state-of-the-art in sustainable energy technologies key to tackling the world's energy challenges and achieving environmentally benign solutions. Its unique amalgamation of the latest technical information, research findings, and examples of successfully applied new developments in the area of sustainable energy will be of keen interest to engineers, students, practitioners, scientists, and researchers working with sustainable energy technologies.  Problem statements, projections, new concepts, models, experiments, measurements, and simulations from not only engineering and science, but disciplines as diverse as ecology, education, economics, and information technology are included, in order to create a truly holistic vision of the sustainable energy field. The contributions feature coverage of topics including solar and wind energy, biomass and biofuels, waste-to-energy, renewable fuels, geothermal and hydrogen power, efficiency gains in fossil fuels and energy storage technologies such as batteries and fuel cells.